12‐OH‐17, 18‐Epoxyeicosatetraenoic acid alleviates eosinophilic airway inflammation in murine lungs. Issue 2 (25th September 2017) - Mochimaru, T.; Fukunaga, K.; Miyata, J.; Matsusaka, M.; Masaki, K.; Kabata, H.; Ueda, S.; Suzuki, Y.; Goto, T.; Urabe, D.; Inoue, M.; Isobe, Y.; et al.
Abstract: Background: Asthma is characterized by airway inflammation and obstruction with eosinophil infiltration into the airway. Arachidonic acid, an omega‐6 fatty acid, is metabolized into cysteinyl leukotriene with pro‐inflammatory properties for allergic inflammation, whereas the omega‐3 fatty acid eicosapentaenoic acid (EPA) and its downstream metabolites are known to have anti‐inflammatory effects. In this study, we investigated the mechanism underlying the counter‐regulatory roles of EPA in inflamed lungs. Methods: Male C57BL6 mice were sensitized and challenged by ovalbumin (OVA). After EPA treatment, we evaluated the cell count of Bronchoalveolar lavage fluid (BALF), mRNA expressions in the lungs by q‐PCR, and the amounts of lipid mediators by liquid chromatography‐tandem mass spectrometry (LC‐MS/MS)‐based lipidomics. We investigated the effect of the metabolite of EPA by in vivo and in vitro studies. Results: Eicosapentaenoic acid treatment reduced the accumulation of eosinophils in the airway and decreased mRNA expression of selected inflammatory mediators in the lung. Lipidomics clarified the metabolomic profile in the lungs. Among EPA‐derived metabolites, 12‐hydroxy‐17, 18‐epoxyeicosatetraenoic acid (12‐OH‐17, 18‐EpETE) was identified as one of the major biosynthesized molecules; the production of this molecule was amplified by EPA administration and allergic inflammation. Intravenous administration of 12‐OH‐17, 18‐EpETE attenuated airway eosinophilic inflammation through downregulation of C‐C chemokine motif 11 ( CCL11 ) mRNA expression in the lungs. In vitro, this molecule also inhibited the release of CCL11 from human airway epithelial cells stimulated with interleukin‐4. Conclusion: These results demonstrated that EPA alleviated airway eosinophilic inflammation through its conversion into bioactive metabolites. Additionally, our results suggest that 12‐OH‐17, 18‐EpETE is a potential therapeutic target for the management of asthma.